Intratesticular and intraovarian epidermoid inclusion cysts: report of two cases - Guilherme José Morgan; Taniela Marli Bes; Ingrid Berger Severo; Eduardo de Barros Coelho Bicca; Heitor Alberto Jannke (Sociedade Brasileira de Patologia Clínica, 2013)
Two rare cases of intragonadal epidermoid inclusion cysts are described. Their etiology remains controversial and a possible hypothesis is monodermal abortive teratomas, with no mesodermal and endodermal components. As the ultrasound test results were inconclusive, it became difficult to rule out the possibility of neoplasm. Therefore, patients were submitted to radical therapy. The definitive diagnosis for both cases was provided by the anatomopathological examination.